The contribution of self-beliefs to the mathematics gender achievement gap and its link to gender equality - Sakellariou, Chris (2021)
I brought together two strands of literature, one investigating the moderate but persistent underachievement of girls in mathematics in most countries, and the other examining the role of self-efficacy and other self-beliefs in predicting behaviour and achievement. I implemented detailed decompositions of the gender mathematics gap, both at the mean and for low and high performing students, for a large and diverse group of countries. I found considerable heterogeneity and different cross-country patterns in decomposition components and the contribution of self-beliefs. In OECD-Europe and more affluent East Asian countries, most or all the gap is explained by gender differences in self-efficacy; on the other hand, in Latin America and the Middle East, most of the gap remains unexplained. I also investigated the relationship between the gender mathematics gap-gender equity relationship across countries and found that a clearly negative association between the size of the gap and gender equality in a cross-country regression can be established after controlling for cross-country heterogeneity in gender differences in mathematics self-beliefs, which correlate with gender equality.